Herakles and Hercules : exploring a Graeco-Roman divinity - Rawlings, Louis; Bowden, Hugh (Classical Press of Wales ; Distributor in the United States of America, the David Brown Book Co., 2005)
"Herakles and Hercules: two names for a figure of pervasive appeal in Antiquity. The eleven new studies in this volume explore why this figure appealed so widely in Antiquity. They examine his role in ancient myth and philosophy, drama and art, as well as in politics and propaganda, warfare and religion."--Jacket